GENDER PROBLEM IN FAMILY BUSINESS - Sentot Imam Wahjono (UMSurabaya Publishing, 2011)
The role of family business the economy are enormous, both in term of contribution in GNP and employment. Many world class companies such as motorla, Nordstrom, Bakrie, Gudang Garam maintain as a family business even though they have been going public in the capital markets. Perception of the global community is more like men as a manager and controller of the business than women. Male primogenitur is the adagium to describe how men are very dominant in the business world. In the USA and South Korea man is the successor of the family business. Japan rejected the role of women in the family business so that all inheritance fell on one of the sons. In China, the company inherited fell on the whole boys shared equality. In Turkey, female successor only 4.2%. Nevertheles, quite a lot of women who own the company. In USA there are 8 million women-owned family business, in Japan 23%, Australia 33%, Canada 31%, Mexico 16%, and Netherlands 15%. The imbalance in gender equity and equality in the family business was global perceived. In Indonesia takes efforts to open wider access for Indonesian women in the domain corporate management, expand the participation of women, increase the role of controlling, adding to the usefulness in the management of family business that have sustainable resilience in the face of global competition. Key-words: family business, gender, male primogeniture.